Nurses' awareness and compliance on Waste Reduction Action Program (WRAP) - Balingbing, Lilia Vargas
Managing wastes in any setting poses problems to the administrator, as well as in healthcare setting.The primary focus of the study was to evaluate the level of awareness and extent of compliance of nurses on waste management in a tertiary government hospital. Likewise, the effect of Waste Reduction Action Program (WRAP) to their awareness and compliance.The study wishes to minimize public risks by educating healthcare providers as well as its clientele on waste management particularly on the MMDA Ordinance No. 16.A one group quasi - experimental design was utilized in this study sample consisted of nurses from DPPS and Service Wards of a tertiary government hospital. The subjects were chosen through multistage random sampling.The study used only one set of questionnaire for pre and post test following the Likert Scale and evaluated through a 5-point Scale Checklist.Results showed that there is a full awareness on waste management among the participants, and good compliance as well. The use of Pearson' r and chi-square at the preset level of significance of 0.05 showed that the level of awareness and extent of compliance of participants on waste management are associated with the position they held and their area of assignment.The study was able to draw the following conclusions: (1)Nurses have full level of awareness and good compliance on waste management. (2) Position and the area of assignment of nurses are factors that are related to the level of awareness and extent of compliance of nurses, (3) the implementation of Waste Reduction Action Program (WRAP) increases nurses' awareness and compliance on waste management.Results of this study encourage and enlighten policy makers to focus on safety of every employee and promote cost effectiveness to the institution.